Silibinin from Silybum marianum Stimulates Embryonic Stem Cell Vascular Differentiation via the STAT3/PI3-K/AKT Axis and Nitric Oxide - Ali, Enas Hussein; Sharifpanah, Fatemeh; Wartenberg, Maria; Sauer, Heinrich (Planta Medica, 2018)
Silibinin, the bioactive compound of milk thistle (Silybum marianum), exerts tissue protective and regenerative effects that may include stem cell differentiation toward vascular cells. The purpose of the present study was to investigate whether silibinin stimulates blood vessel formation from mouse embryonic stem (ES) cells and to unravel the underlying signaling cascade. Vascular branching points were assessed by confocal laser scanning microscopy and computer-assisted image analysis of CD31-positive cell structures. Protein expression of vascular markers and activation of protein kinases were determined by western blot. Nitric oxide (NO) generation was investigated by use of the fluorescent dye 4-amino-5-methylamino-2′,7′-difluorofluorescein diacetate. Silibinin dose-dependently increased CD31-positive vascular branching points in embryoid bodies cultivated from ES cells. This was paralleled by increase of protein expression levels for the endothelial-specific markers vascular endothelial cadherin (VE-cadherin), vascular endothelial growth factor receptor 2, and hypoxia-inducible factor-1α. Moreover, silibinin increased activation of endothelial nitric oxide synthase (eNOS), which boosted generation of NO in embryoid bodies and enhanced phosphorylation of signal transducer and activator of transcription 3 (STAT3) as well as phosphoinositide 3-kinase (PI3-K) and AKT. Vasculogenesis, VE-cadherin expression, STAT3 and AKT phosphorylation, NO generation, and eNOS phosphorylation were inhibited by the small molecule STAT3 inhibitor Stattic, AKT inhibitor VIII, the PI3-K inhibitor LY294002, or the NOS inhibitor Nω-Nitro-L-arginine methyl ester hydrochloride. In conclusion, our findings indicate that silibinin induces vasculogenesis of ES cells via activation of STAT3, PI3-K, and AKT, which regulate NO generation by eNOS.
Keywords: Silybum marianum; Asteraceae; silibinin; embryonic stem cell; vasculogenesis; nitric oxide; STAT3; AKT